1981
DOI: 10.1037/0735-7028.12.1.56
|View full text |Cite
|
Sign up to set email alerts
|

Sex roles and unwanted pregnancy in adolescent and adult women.

Abstract: Many women each year experience an unwanted pregnancy that creates stresses for them, for their partners and families, and for health professionals. Psychologists may be able to reduce the likelihood of unwanted pregnancy as well as contribute to a constructive resolution of the crisis associated with its occurrence. 'This article highlights factors that are often associated with contraceptive use and nonuse. 7 he effects of sex roles are considered, and it is shown that socialization in traditional sex roles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Similarly, traditional sex role stereotypes may be less pronounced in couples where both the man and the woman have a fairly high level of education [ 121. More specifically, previous studies [13,14] have found less conventionally sex typed women to be better contraceptors, which may be due to the fact that they do not believe the man to be the protector-responsible partner and the woman to be passive and dependent.…”
Section: Discussionmentioning
confidence: 90%
“…Similarly, traditional sex role stereotypes may be less pronounced in couples where both the man and the woman have a fairly high level of education [ 121. More specifically, previous studies [13,14] have found less conventionally sex typed women to be better contraceptors, which may be due to the fact that they do not believe the man to be the protector-responsible partner and the woman to be passive and dependent.…”
Section: Discussionmentioning
confidence: 90%
“…For individual women, however, the best predictors of pregnancy are those associated with (1) opportunity, which is influenced by factors such as marital status and age at marriage, and (2) the likelihood of using contraception, which is influenced by factors such as access to family planning services, employment status, and communication with partner. Adler (1981) described a constellation of traits and situational factors that appear to make unplanned pregnancies more likely. Women who become pregnant accidentally often have weak feelings of self-competence and control, a conflict over their own sexuality, a desire to demonstrate their adulthood, and a lack of career goals.…”
Section: Introductionmentioning
confidence: 99%
“…Leventhal (1986) introduced the notion that patient perceptions and mental representations were key antecedents to symptom interpretation, health behavior, and adherence. Adler (1981) was an early leader in understanding psychological dimensions of reproductive health and contraceptive use. Pennebaker conducted groundbreaking work on symptom reports (e.g., Pennebaker & Skelton, 1981) and on the effect of expressive writing about traumatic experiences on well-being (Pennebaker, 1989).…”
Section: Historical Contextmentioning
confidence: 99%